Rancangan Hypothetical Learning Trajectory (HLT) Menggunakan Konteks Perubahan Iklim untuk Melatih Kemampuan Literasi Statistik - Friansah, Drajat; Zulkardi, Zulkardi; Susanti, Ely; Nusantara, Duano Sapta (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2024)
The issue of climate change is a global problem that is very strategic to be overcome, because it has an impact on the environment. Low ability to understand and interpret climate change data presented statistically is associated with low statistical literacy skills. Statistical literacy is the critical ability to access, understand, interpret, and evaluate statistical information or messages in various contexts. This underlies researchers to design learning trajectories using the context of climate change to train the statistical literacy skills of prospective teacher students. The method used is the design of research type validations studies with the subject of prospective teacher students. This research produced HLT which is able to facilitate statistical literacy skills and successfully identify the level of statistical literacy ability of students who are at low and middle stages.